The accreditation of engineering programmes in Russia; European Journal of Engineering Education; Vol. 29, Issue 1 (March) - Pokholkov Y. P. Yuri Petrovich; Chuchalin A. I. Alexander Ivanovich; Morozova E. A.; Boev O. V. (2004, 2004)
The paper is devoted to the national accreditation system for engineering programmes in the Russian Federation. The procedure for the integrated assessment of university activities provided by the Ministry of Education is described. The paper examines licensing and attestation requirements for achieving the state accreditation. The procedure and criteria for professional accreditation of educational programmes in engineering and technology are presented, as well as the latest activities of the Russian Association for Engineering Education.